THE IMPACT OF THE REVITALIZATION OF MOTANG RUA FIELD IN RUTENG CITY ON THE DEVELOPMENT OF THE CREATIVE ECONOMY IN MANGGARAI REGENCY - Murdian, Maria Herkulani; Tiwu, Maria Indriyani Hewe; Sili, Maria Antonia Radji (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to analyze the impact of the revitalization of Motang Rua Field in Ruteng City on the development of the creative economy in Manggarai Regency. The revitalization of this public space was intended to enhance the social and economic functions of an area that had previously been underutilized. Using a quantitative approach through correlation analysis of 40 respondents involved in the creative economy, including MSMEs, as well as a qualitative approach employing SWOT analysis from 20 key informants, the study found that the revitalization significantly contributed to the growth of creative economic activities, particularly in the culinary, crafts, and performing arts subsectors. The results show increased community participation, local economic circulation, and MSME growth in the vicinity of Motang Rua Field. Additionally, the local government's development strategies included the provision of supporting infrastructure, strengthening of local tourism promotion, and active engagement of creative communities. These findings affirm that public space revitalization, when designed in a participatory and sustainable manner, can serve as a catalyst for building a creativity-based local economy. The study provides recommendations for local governments in formulating policies that support the sustainability of public spaces and the creative economy in other regions with similar conditions.